2020
DOI: 10.1088/1742-6596/1679/5/052018
|View full text |Cite
|
Sign up to set email alerts
|

Methods and algorithms for investigating noise and errors in the intelligent measuring channel of control systems

Abstract: The main requirements for an intelligent measuring channel are considered in the article when designing automated control and control systems. The methods for estimating errors are classified and the constituent groups are classified, and some methods for calculating the errors of measuring means and measuring modules of automatic control systems are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…from which it follows: To illustrate the application possibilities of the proposed approach, let's consider the results of a specific model research [7][8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…from which it follows: To illustrate the application possibilities of the proposed approach, let's consider the results of a specific model research [7][8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…An observer is used to estimate the disturbance and its derivatives, and a special signal is generated for this purpose, which allows obtaining the corresponding estimates. A similar problem is also solved in [7][8][9][10][11], but with known parameters of the controlled system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to reduce the error and improve the reliability of the developed magnetic modulation DC converters, the most acceptable method is the majority reservation using a majority body with an odd number of inputs. In this case, the reduction of the conversion error is achieved by reducing the standard deviation of the output signal from its average value [9]. It is shown that if for the known magnetic modulation DC converters with an open NFBM circuit the maximum error was about 2% of the maximum signal, then with a closed NFBM circuit, a constant static transmission coefficient and an increased MMF of the input circuit of the converter due to the manufacture of the magnetic system in the form of several coaxially arranged toroidal cores interconnected by diametral jumpers, this error was already about 0.74%.…”
Section: Resultsmentioning
confidence: 99%
“…A sawtooth voltage is supplied to the inputs of null-organs from a sawtooth voltage generator (SVG). Due to the fact that MP is an averaging element that transmits the average value of the input signal to the output, then with the majority redundancy, an increase in the reliability and accuracy of the output signal from its average value [9].…”
Section: Methodsmentioning
confidence: 99%
“…In order to ensure the stability of the filter, it is necessary | < 1, 2 < 1 and, accordingly, 2 > вх 2 , the more tends to 1, the more the input noise level will increase filter [11].…”
Section: Main Partmentioning
confidence: 99%